Real-world safety profile of live attenuated Japanese encephalitis vaccine before and after the vaccine administration law - Chao Zhang; Yan Liu; Xiaofu Luo; Liping Han; Jianyong Shen (PLoS ONE, 2025)
Purpose Live attenuated Japanese encephalitis vaccine (JEV-L) was included in the Expanded program on immunization on Immunization (EPI) in 2008 and has had a satisfactory effectiveness and safety profile in protecting children from JE virus infection. This study was designed to evaluate the surveillance sensitivity and changes over time of adverse event following immunization (AEFI) reports related to JEV-L based on the national AEFI surveillance system(NAEFISS) data before and after the introduction of vaccine administration law (LAW) from 2014 to2023 in Huzhou City. Methods AEFI data were collected from NAEFISS from 2014 to 2023 and included age, AEFI and diagnostic categories. AEFI incidence rates are calculated/10,000 vaccine doses and a reporting odds ratio −1.96 standard error (ROR-1.96SE) >1 defined a positive signal between AEFI and vaccine. We categorized the time interval into the pre-LAW period (2014–2019) and post-LAW period (2020–2023) to demonstrate the impact of LAW on the surveillance of AEFI. Results The NAEFISS collected 225 AEFI reports after administering 599,223 doses of JEV-L, with a AEFI reported rate of 3.75/10,000 doses. Overall AEFI reported rates increased over time with a drop in 2020 (P < 0.001, χ2 for trend). The reported rate of AEFI in post-LAW period was higher than that in the pre-LAW period (P < 0.001), accounted for increases in fever, local redness and local induration. However, the reported rate of urticaria decreased significantly in post-LAW period(P = 0.043). This study found a positive signal association between JEV-L immunization and fever in the pre- (1.394) and post-LAW period(2.833) and a signal for urticaria in the pre-LAW period (2.098). There were only 2 severe reactions reported: thrombocytopenia and epilepsy. Conclusions The implementation of the LAW significantly enhanced the surveillance capacity and sensitivity for AEFIs associated with JEV-L. This study did not find any new/unexpected safety concern in the post-LAW period. Severe reactions remain rare despite the greatly improved sensitivity of surveillance, indicating that the vaccine was comparatively safe. However, continuous epidemiological investigation are needed to systematically assessment the data provided by NAEFISS.